Managerial Challenges Related to the Efficient Use of Energy Resources in the Hotel Industry - Ana-Maria Nica; Andreea Raceanu; Mihail-Ovidiu Tanase; GabrielaTigu (Amfiteatru Economic, 2023)
Management commitment and perception of the need to adapt and adjust hotel operations in the face of the energy crisis on the path of reducing energy consumption under the REPowerEU plan have been little addressed in the literature, although it is a very topical issue. This research fills this gap with a qualitative study aimed at analysing the way hotel managers in Bucharest perceive the energy crisis. The research questions were related to how the energy crisis affects their operational activities and what measures were taken to reduce energy consumption and change business behaviour. The method chosen was the semi-structured interview in order to obtain complex and detailed answers based on direct interactions at the individual level, given the profile of the interviewees (top managers). The thematic analysis method was used to analyse and interpret the responses recorded in the interviews. As important results of the study, it is worth mentioning: the highlighting of the perception of the energy crisis and its impact at the level of the hotel units, but above all, the identification of the measures implemented or sought by the management of the hotel units to reduce energy consumption (such as the monitoring of consumption, integrated systems for managing consumption and maintenance, the involvement of employees, but also of customers, and last but not least, the investment in alternative energy sources).
Keywords: Z31; Q49; Q38; P28; O14; M14; L83; D22; 330; Bucharest hotels; energy savings; energy efficiency; managerial perceptions; energy crisis.